Leadership Styles of Head teachers in Relation to Teachers' Job Satisfaction: A Case Study of the Volta Region - Ghana - Gakpoh, Sampson Kwaku; Maison, Regina Sally; Boe-Doe, Kennedy; Kwafo, Alexander Djan (Journal of Advanced Psychology, 2024)
Purpose: The present study focuses on exploring the leadership styles of basic school headteachers, and their effects on teachers' job satisfaction in Ghana's Volta region. Methodology: Two research questions and one hypothesis guided the study. The study adopted a descriptive research design. The study was conducted in the Volta region of Ghana. The population of the study are 3,009 headteachers and 17,889 teachers in the 18 districts in the Volta Region. The sample size of the study was 191 headteachers and 328 teachers. Multi-stage sampling technique was used to draw the sample size. The Multifactor Leadership Questionnaire (MLQ) and Mohrman-Cooke-Mohrman Job Satisfaction Scale (MCMJSS) was adopted for the study. Findings: It was found that headteachers identified moderate levels of transformational, transactional, and laissez-faire as the leadership styles adopted by headteachers. Also, the majority of the headteachers had a very low level of job satisfaction whereas the majority of the teachers had a very high level of job satisfaction. Among the three leadership styles, transformational (Î² = .47, p < .001) and laissez-faire leadership styles (Î² = .19, p = .002) were the only significant predictors of job satisfaction. Both transformational and laissez-faire forms of leadership were positive predictors of job satisfaction. Unique Contributor to Theory, Policy and Practice: The results shows that headteachers identified moderate levels of transformational (M = 7.68, SD = 0.83), transactional (M = 7.51, SD = 1.15), and laissez-faire (M = 6.94, SD = 1.89) as the leadership styles adopted by headteachers. It shows that 128 (71.9%) of the headteachers had a very low level of job satisfaction, while 30 (16.9%) had a very high level of job satisfaction. On the contrary, 153 (52.8%) of the teachers had a very high level of job satisfaction while 21 (7.1%) had a very low level of job satisfaction. The three leadership styles; transformational (Î² = .47, p < .001) and laissez-faire leadership styles (Î² = .19, p = .002) were the only significant predictors of job satisfaction. Both transformational and laissez-faire forms of leadership were positive predictors of job satisfaction. Based on the findings of the study, relevant conclusions were drawn.